Extra-genital lichen sclerosus reminiscent of cut dragon fruit. - Inamadar, A.C. (European Journal of Pediatric Dermatology, 2020)
Extra-genital lesions of lichen sclerosus et atrophicus (LS) may occur anywhere on the body. The lesions are polygonal, bluish-white papules that coalesce to become atrophic plaques (2). Prominent, evenly spaced follicular plugs in the atrophic plaques corresponding to obliterated follicular ostia are characteristically seen in the early stages of LS (2). With time, the plugs disappear and leave a smooth, porcelain-white plaque. Dragon fruit is an exotic cactus that is found in Asia, Mexico, and parts of South America (1). The inside pulp of each cut piece of fruit is filled will small seeds that look similar to the follicular plugs of the early stages of LS. The similarities with living beings of dermatological lesions are the basis of many terms such as lupus, herpes etc.